Education Improvement Promoting Human Capabilities Development in Post-Neoliberal Period - St. John, Edward P.; Chen, Luxi; Taylor, Zachary; Yang, Lijing; Wang, Chen (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue is dedicated to Dr. Patricia Somers (22 April 1949-10 March 2023). Pat was a proud mother, feminist educator, devoted colleague, and beloved mentor for her students. Above all, she advocated for the underserved and minoritized, including investing time in her students who were up against considerable institutional odds. Pat was also a driving force for social justice in the United States, Brazil, and across the world, as her scholarship prioritized giving voice to the voiceless and advocating for racial and gender equity. As an editorial team, we honor and celebrate Dr. Somers' vibrant and impactful life with this Special Issue, in the hopes that future generations of educators follow her lead and promote diversity, equity, and inclusion. Rest in peace and in power, Pat. We will miss you always.